Health and wellness tourism in Sicily: development and enhancement. (30th September 2020) - Arnone, R; Bue, S L; Parenti, I
Abstract: Background: The Health Counselor of Sicily in Italy, appointed the "Forum Meridiano Sanità" 2020 dedicated to Health Tourism (HT). Sicily is a member of the Italian network "Mattone internazionale salute" that focus the development of Health Tourism aiming at: Establish the state of art on HT; Defining a strategy to give visibility of the services targeting health tourists; Defining joint actions/projects to strengthen Italy's attractiveness and the action plan to promote/valorize health performances and the touristic services offered. Sicily, making use of its cultural/environmental characteristics, landscapes, climate, food traditions and its Mediterranean diet, wants to be accounted for a destination on health/wellness tourism. Target groups are seniors, disabled people and people affected by particular pathologies Contribution of Sicilian Region (Sicilian Health Government and CEFPAS) and of the European program 2021-2027 are promoting in Sicily the implementation of such in the development of the "Health and Wellness Tourism". In order for this to be integrated in a broader framework a discussion on the first European Charter on Health Tourism will be developed with participants. Results: The "working table" has elaborated a document "Framework on health and tourism - the interregional point of view" containing the definitions of Health tourism, a state of art of the national/European legislative framework and a mapping of the touristic flow and the needs of seniors. The Regional Health Government is also starting articulations with other Regional Governments (e.g. Tourism/Environment). Strategic alliances/resources able to transform the tourism sector, should focus a strategic policy agenda for health prevention/promotion linked to a wider concept of general wellness. Key message: Promote health/wellness tourism targeting seniors and people with disabilities/pathologic diseases is considered worth the investment.